2023
DOI: 10.1111/ijac.14536
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic modulation of ferroelectric polarization and relaxor behavior of Sr2NaNb5O15‐based tungsten bronze ceramic

Peixiaokan Si,
Peng Zheng,
Xinzhong Zhang
et al.

Abstract: Developing dielectric ceramics with high energy storage performance (ESP) is essential for miniaturizing and integrating high‐power pulse capacitors. Sr2NaNb5O15‐based tungsten bronze ferroelectric ceramics have been highly investigated for dielectric energy storage applications recently. However, the difficulty in concurrently obtaining large polarization and strong relaxor characteristics greatly hinders the ESP improvement. In this work, Bi3+ and Ti4+ ions were introduced into the Sr2NaNb5O15 ceramic, aimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…It is noteworthy that the sample consistently exhibits slender P–E loops thanks to its robust thermal stability, the decrease in W rec and η remains below 3 and 4%, respectively, throughout the tested temperature range. In Figure i, a comparison of W rec and η between KBBNTP-2T GCs and various other tungsten bronze ceramics and glass ceramics is presented. , Figure S13 also shows the stability of the KBBNTP-2T GCs sample in terms of different frequencies and cycle numbers. It can be seen that this sample shows a certain degree of stability.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the sample consistently exhibits slender P–E loops thanks to its robust thermal stability, the decrease in W rec and η remains below 3 and 4%, respectively, throughout the tested temperature range. In Figure i, a comparison of W rec and η between KBBNTP-2T GCs and various other tungsten bronze ceramics and glass ceramics is presented. , Figure S13 also shows the stability of the KBBNTP-2T GCs sample in terms of different frequencies and cycle numbers. It can be seen that this sample shows a certain degree of stability.…”
Section: Resultsmentioning
confidence: 99%
“…6(e). 2–4,10,13,16,18,19,29–40,55 Furthermore, this ceramic shows a leading position in terms of stored/released energy per gram, and the parameter W rec / ρ (density) was subsequently introduced as a figure of merit to assess the lightweight capability. Ceramics reported in recent publications and this work are compared in terms of unit volume ( W rec ) and unit mass ( W rec / ρ ) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tetragonal tungsten bronze (TTB) ferroelectrics, which have a general formula of (A1) 2 (A2) 4 (C) 4 (B1) 2 (B2) 8 O 30 , feature excellent optoelectrical performance, pyroelectric properties, and piezoelectric properties. 28–37 Their abundant ion sites provide rich compositional diversity, attracting widespread research attention. Recent research progress has shown that TTB-based ceramics can achieve outstanding ESP due to their structural tunability based on which their ferroelectric behavior can be adjusted.…”
Section: Introductionmentioning
confidence: 99%